Do Infrastructure Reforms Reduce the Effect of Corruption? Theory and Evidence from Latin America and the Caribbean - Wren-Lewis, Liam (World Bank, Washington, D.C., 2013)
This paper investigates the interaction between corruption and governance at the sector level. A simple model illustrates how both an increase in regulatory autonomy and privatization may influence the effect of corruption. The interaction is analyzed empirically using a fixed-effects estimator on a panel of 153 electricity distribution firms across 18 countries in Latin America and the Caribbean from 1995--2007. Greater corruption is associated with lower firm labor productivity, but this association is reduced when an independent regulatory agency is present. These results survive a range of robustness checks, including instrumenting for regulatory governance, controlling for a large range of observables, and using several different corruption measures. The association between corruption and productivity also appears weaker for privately owned firms compared to publicly owned firms, though this result is somewhat less robust.